Optimal levels of sleep, sedentary behaviour, and physical activity needed to support cognitive function in children of the early years - Samah Zahran; Dylan P. Cliff; Devan Antczak; Eivind Aadland; Katrine N. Aadland; Jade Burley; Valerie Carson; Catherine E. Draper; Dorothea Dumuid; Nicholas Kuzik; Diego Augusto Santos Silva; Esther M. F. van Sluijs; et al. (BMC Pediatrics)
Abstract Background Sleep, sedentary behaviour, physical activity, and the composition of these movement behaviours across the 24-h day are associated with cognitive function in early years children. This study used a Goldilocks day compositional data analysis approach to identify the optimal duration of sleep, sedentary behaviour, light physical activity, and moderate-to-vigorous physical activity associated with desired cognitive function outcomes in early years children. Methods This cross-sectional study included 858 children aged 2.8–5.5 years from the Sleep and Activity Database for the Early Years. 24-h movement behaviours (sleep, sedentary behaviour, light physical activity, moderate-to-vigorous physical activity) were measured using ActiGraph accelerometers. Cognitive function was measured using three tasks from the Early Years Toolbox: visual-spatial working memory, response inhibition, and expressive vocabulary. A Goldilocks day compositional data analysis approach was used in R software to identify the optimal time-use compositions associated with the best 10% of the cognitive function scores. Results The movement behaviour composition and the relative time spent in sleep and sedentary behaviour but not different intensities of physical activity were significantly associated with working memory (P ≤ 0.01). The movement behaviour composition and relative time spent in sleep, sedentary behaviour, and different intensities of physical activity were not significantly associated with response inhibition or expressive vocabulary (P > 0.2). Therefore, optimal time use was only determined for working memory. Optimal daily durations for working memory were observed with 11:00 (hr:min) of sleep, 5:42 of sedentary behaviour, 5:06 of light physical activity, and 2:12 of moderate-to-vigorous physical activity. Conclusion Working memory was the only cognitive function outcome related to the 24-h movement behaviour composition. Optimal sleep for working memory was consistent with current recommended durations, while optimal moderate-to-vigorous physical activity greatly exceeded minimal recommended levels. Optimal sedentary behaviour was longer and light physical activity was shorter than the sample average.